ADOPTER CATEGORY AND PREFERENCE OF INFORMATION SOURCE ON THE ADOPTION OF HERBAL FEED ADDITIVE ON BROILER FARM - Ayu Intan Sari (UNEJ e-Proceeding, 2012)
The first aim of this research is to analyze the effect of social economic characteristics and communication behavior of the farmer on the probability of adopter category differences and on the preference of source of information. The second aim is to analyze the effect of adopter category on the preference of source of information. This research has been conducted in the broiler farm at Karanganyar, Sragen, and Boyolali Central Java by using research based method of descriptive analysis. The result of the research shows that there are differences in social economic characteristics and communication behavior of the farmer between early and late adopter categories; they are age (p0.01), formal education level (p0.01), cosmopoliteness level (p0.01), and farming experience (p0.05). The result of logistic binominal regression test on social economic characteristics shows that age and formal education level influence the difference of adopter category significantly (p0.05). The characteristics of farmers haveeffect on the preferences of personal and non personal information source, namely age, formal education level, and cosmopoliteness level, which have significant effect (p0.05). Additionally, the result shows that the adopter category has very significant effect (p0.01) on the preference of information source. The conclusion of the research is that the younger farmers, higher formal education level, longer experience, and higher level of active searching information seemed to have higher probability to become the early adopter. The farmers have higher preference on non personal information source.